2022
DOI: 10.1136/bmjsem-2022-001343
|View full text |Cite
|
Sign up to set email alerts
|

Lateral abdominal muscles of adults with hypermobility may be partially impaired during contraction

Abstract: BackgroundMuscle function may be impaired in people with generalised hypermobility, yet prior studies have primarily focused on muscles within the extremities. We aimed to examine changes in lateral abdominal muscle (transversus abdominis (TrA) and the external (EO) and internal abdominal obliques (IO)) thickness and length during contraction between participants with and without hypermobility.MethodsThis cross-sectional study examined 12 participants with hypermobility and 12 age-matched, sex-matched, height-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In our study, individuals with GJH showed lower back muscle static strength endurance compared with the non-GJH group. No scientific data could be found comparing static strength endurance of trunk muscles (abdominal and back) between GJH and non-GJH subjects; however, there is scientific evidence that persons with joint hypermobility have partially impaired lateral abdominal muscle function given a lesser ability to increase transversal abdominal muscle thickness during contraction compared with those without joint hypermobility [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, individuals with GJH showed lower back muscle static strength endurance compared with the non-GJH group. No scientific data could be found comparing static strength endurance of trunk muscles (abdominal and back) between GJH and non-GJH subjects; however, there is scientific evidence that persons with joint hypermobility have partially impaired lateral abdominal muscle function given a lesser ability to increase transversal abdominal muscle thickness during contraction compared with those without joint hypermobility [ 52 ].…”
Section: Discussionmentioning
confidence: 99%